Engineering materials and manufacturing processes from Qur'anic perspective - Haque, Md. Mohafizul; Ismail, Ahmad Faris (Trans Tech Publications Ltd., Switzerland, 2010)
Any useful object is commonly made from selected engineering materials with proper shape and dimension. The selection of materials and manufacturing processes is an important criterion towards the production of useable and affordable objects. The technologies behind this knowledge are needed to acquire through study, proper education, practical training and scientific research related to Materials and Manufacturing Engineering (MME). Allah (swt), the sources of all power and knowledge, has bestowed the Guide Book, the Holy Qur’an through His beloved Messenger Prophet Mohammad (pbuh) to the mankind. Allah (swt) narrated various stories in many Surahs of the noble Qur’an related to applied science and technology. This paper is an attempt to view the integration between the revealed knowledge and the science and technology based knowledge related to engineering materials and manufacturing processes. Finally, stresses have been given to acquire knowledge on science and technology based education and understanding, and disseminate it for the cause of humanity.